PERAN KOMUNIKASI PUBLIK UNTUK MENGATASI KENDALA FEAR OF REJECTION SEBAGAI PEMBICARA (STUDI PADA PUBLIC SPEAKER MEYRINDA TOBING DAN RIANI) - Tiyas Dervi Anggraini; Zusyana Dewi, Ratnaningrum; Ningsih, Masnia (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2021)
This study examines the role of public communication in overcoming the constraints of fear of rejection as a speaker (a study on public speakers). The problem that becomes the focus of this research is the role of public communication to overcome the constraints of fear of rejection as a speaker. The method used in this research is a qualitative method with descriptive research type. This study used two informant subjects, namely Meyrinda Tobing and Riani. This research uses the communicator theory, dramaturgy theory and public speaking theory. Data collection techniques in this study were direct observation, in-depth interviews, literature review and document analysis. While the analysis technique used is the technique of checking the validity of the triangulation data. The results showed that the role of public communication in overcoming the constraints of fear of rejection as a speaker based on the communicator theory is very influential because the ability in communicators who have public speaking knowledge greatly affects the course of an event. In dramaturgy theory, a public speaker is very influential in playing his role on the stage, by having a strategy including creating personal branding. Whereas in the theory of public speaking, the role of a public speaker in overcoming the constraints of fear of rejection must be overcome by mastering the basic science of public communication, having a communication strategy and preparing mentally. Someone who experiences fear of public speaking is triggered because of the factor that he has failed when speaking in public. , mentally that is not built in a person will trigger a sense of fear of rejection to continue to grow. The role of public communication can increase self-confidence, this can increase confidence in one's own abilities so that they are able to face everything calmly, and avoid feeling nervous or worried when communicating in public